Système de reconnaissance des plaques d’immatriculation - Aribi, Zakia; Belbey, Medjda; Ben Ali, Radja (university of eloued جامعة الوادي, 2016)
نظام التعرف التلقائي على لوحات الترقيم هو برنامج فعال ..اصبح في الفترة ال ا رهنة مطلوبا في العديد من المجالات مثل حركة السير حماية الطرقات تسير حضيرة السيا ا رت والسعي و ا رء المجرمين في هاته المذكرة نقدم برنامج للتعرف على لوحات الترقيم وكأي برنامج سوف نمر على عدة م ا رحل بحيث تعتمد المرحلة الاولى على الاستخ ا رج من الصورة التي تكون على المستوى الرمادي بحيث تكون هاته الصورة مأخوذة عن طريق كامي ا ر رقمية او هاتف محمول تتركز اللوحة الرقمية على منهجية التعرف عن طريق le seuillage, la الحدود بحيث تمر هاته اللوحة على م ا رحل المعالجة وم ا رحل اخرى ما قبل ...الخ المعالجة منها. segmentation ومن هنا تكون الصورة OCR وفي الاخير تخضع الصورة على منهجية تسمى منهجية التعرف الضوئي تحت المعالجة الفعالة والسريعة وتعطي نتائج هاته المعالجة في وقت قصير وسريع جدا في التعرف على الحروف والأرقام.An automatic recognition system robust and effective license plates becomes increasingly a necessity in managing multiple domains such as traffic and road safety, parking management, the pursuit of criminals. In this article we present a system for the recognition of Algerian plates. Like any system of recognition of license plates, we will go through a series of steps. The first is to extract from an image acquired by the gray level digital camera or mobile phone, the plate of the vehicle based primarily on an edge detection method. This plaque undergoes a set of treatment and pre-treatments such as thresholding, the ..etc segmentation, to be analyzed by an optical character recognition (OCR English OCR is optical character recognition). In order to achieve a better result as quickly as possible.
licence mémoire informatique
Keywords: كشف الحدود، لوحة الترقيم، تحديد العتبة; edge detection, OCR, thresholding , license plates, KNN